PENGARUH PERSENTASE ABU SEKAM PADI DAN GULA TEBU GULA TERHADAP KARAKTERISASI MORTAR KURVA KEKUATAN DENGAN KOMPRESI PEMUATAN AKSIAL - Cut Yusnar (Portal: Jurnal Teknik Sipil, 2013)
An experiment was conducted to investigate the characterization of strength Curve as the influence of adding Rice Husk Ash  and Sugar Cane Bagasse Ash under Compressive of axial Loading.  Six series of test specimens which was consist of two series of normal mortal specimens,  two series of rice husk ash mortal specimens  with 10 % and 20 % of cement replacement.  Two series of Sugar Cane Bagasse Ash mortal specimens which was consist of 10 % and 20 % of cement replacement. Test result indicated that the mortar  strength curve of Sugar Cane Bagasse  has higher than strength curve of Rice Husk Ash Specimens and normal Strength  concrete.